La Importancia de la Motricidad Fina en el Grado Pre - escolar del Centro Etno-Educativo Integral Rural Kasutalain (2020)
The preschool stage is perhaps the most crucial time in the child's comprehensive development. At this age, the senses, both external, sight, hearing, touch, smell, taste, as well as internal, that is, those that are activated without direct relationship with other objects, are always stimulated and are in full maturation phase, for which requires the directed manipulation of objects to develop their motor skills. Since children have the possibility of developing various skills that are favored as they grow, motor performance refers to the ability that infants can have when making small and large movements such as crawling, bending over, running and walking, etc.